Structure–Activity Relationship Studies of Pyrrolone Antimalarial Agents. Issue 9 (5th August 2013) - Murugesan, Dinakaran; Kaiser, Marcel; White, Karen L.; Norval, Suzanne; Riley, Jennifer; Wyatt, Paul G.; Charman, Susan A.; Read, Kevin D.; Yeates, Clive; Gilbert, Ian H.
Abstract Previously reported pyrrolones, such as TDR32570, exhibited potential as antimalarial agents; however, while these compounds have potent antimalarial activity, they suffer from poor aqueous solubility and metabolic instability. Here, further structure–activity relationship studies are described that aimed to solve the developability issues associated with this series of compounds. In particular, further modifications to the lead pyrrolone, involving replacement of a phenyl ring with a piperidine and removal of a potentially metabolically labile ester by a scaffold hop, gave rise to derivatives with improved in vitro antimalarial activities against Plasmodium falciparum K1, a chloroquine‐ and pyrimethamine‐resistant parasite strain, with some derivatives exhibiting good selectivity for parasite over mammalian (L6) cells. Three representative compounds were selected for evaluation in a rodent model of malaria infection, and the best compound showed improved ability to decrease parasitaemia and a slight increase in survival.